The Theoretical Reflection of Islamo-Fascism and Darul Islam Movement in Indonesia - Al Chaidar; Teuku Syahrul Ansari; Irfan Iryadi; Dedy Tabrani (Budapest International Research and Critics University, 2019)
This study regarding the theoretical reflection of Islam-fascism and Darul Islam movement in Indonesia. History of Islam in Indonesia is also the history of power struggle (caliphate) which has not been completed until now. At that time Islam respecting plurality and respect the existing culture. The spirit of pluralism and tolerance enforced developed with enriched intellectual repertoire. Increasingly repressive and hegemonic states, bulldoze people across ethnic, class, and layers. Political regimentation of Suharto's New Order devastated spirit of nationality and humanity. Therefore, the intellectuals and the elite of Islam must find a way out of the crises of social, economic, and political ideology today, so that no reform has stagnated, so that this nation does not disintegrate. Giddens called political